Moderasi Beragama Melalui Penguatan Media Siber Aswaja LTN NU Temanggung Sebagai Kontra Radikalisme - Mubarok, Najib; Azizah, Farinka Nurrahmah (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Raden Fatah Palembang, 2023)
The aims of this research are to develop the values ​​of religious moderation through the Aswaja cyber media and to test the Aswaja cyber media as counter-radicalism. The research method used is Participatory Action Research (PAR). The data collection instruments used in this research are focused Group discussions (FGD), observation, and documentation. In this research, it was concluded that Aswaja cyber media at LTN NU Temanggung was very weak. The weakness of Aswaja cyber media is caused by five factors : media ideology, content theme determination, trust, media sustainability, and low content traffic. To overcome the existing problems, training on content, SEO, marketing strategies, and journalistic workshop were carried out. In addition, the media website aswajanesia.com was created as a trial for Aswaja cyber media as counter radicalism